Phenolic composition of Bobal red wines elaborated with prefermentative cold maceration - Aleixandre,J.L. (2012)
The technique called pre-fermentative cold maceration is used to enhance the anthocyanins diffusion from the skins to the must, increasing the pigments extraction. In this study, the influence of the pre-fermentative cold maceration treatments (3 and 5 days) and the time of maceration (7 or 14 days) on color characteristics and phenolic composition of Bobal red wines made from grapes harvested at different phenolic maturity was studied. The results showed the higher the phenolic maturity the higher polymerized tannins, ethanol index and the lower astringency. The prefermentative cold maceration enhanced berry compounds extractability, but led to wines with less polymerized anthocyanins and tannins. Moreover wines with higher tannin concentration, total polyphenols and polymerization degrees were produced with longer maceration times. On the contrary a decrease in colour and anthocyanin concentration was observed. Regarding sensory analysis, it has been highlighted the importance of grape maturity and pre-fermentative cold maceration length on the wine quality.